A Legend of the Dead. - Asong, Linus T. (Linus Tongwo), 1947-2012 (Langaa RPCIG, 2009)
When the admirable Kevin Beckongncho becomes the new Paramount Chief of the much-coveted throne of Nkokonoko Small Monje as well as its new DO, Chieftaincy could finally be said to have been redeemed. But he quickly becomes a marked man, as he runs into fatal collision with an unscrupulous governmental system with which he cannot co-exist. How this great man suddenly dies, and why his people must not mourn for him, is the unresolved mystery with which Asong closes both the book and his trilogy that includes The Crown of Thorns and No Way to Die.